Sustainable green catalysis by supported metal nanoparticles - Fukuoka, Atsushi; Dhepe, Paresh Laxmikant (Chemical Record, 2009)
The recent progress of sustainable green catalysis by supported metal nanoparticles is described. The template synthesis of metal nanoparticles in ordered porous materials is studied for the rational design of heterogeneous catalysts capable of high activity and selectivity. The application of these materials in green catalytic processes results in a unique activity and selectivity arising from the concerted effect of metal nanoparticles and supports. The high catalytic performances of Pt nanoparticles in mesoporous silica is reported Supported metal catalysts have also been applied to biomass conversion by heterogeneous catalysis Additionally, the degradation of cellulose by supported metal catalysts, in which bifunctional catalysis of acid and metal plays the key role for the hydrolysis and reduction of cellulose, is also reported. (C) 2009 The Japan Chemical Journal Forum and Wiley Periodicals, Inc. Chem Rec 9: 224-235: 2009: Published online in Wiley InterScience (www.intersciencewiley.corn) DOI 10.1002/tcr.200900004
Keywords: Biomass; cellulose; CO oxidation; Mesoporous silica; supported metal catalyst